Ultrasonic melt processing upon direct-chill casting of aluminium alloys. Issue 1 (1st January 2023) - Eskin, D G; Subroto, T; Priyadarshi, A; Beckwith, C; Pericleous, K; Tzanakis, I
Abstract: Ultrasonic melt processing (USP) has been known for decades for beneficial effects in as-cast aluminium alloys, including degassing, grain and structure refinement. In the last 10 years the authors performed a series of research projects dedicated to understanding the nature of these effects, by dedicated advanced experiments and by developing numerical models that adequately reflect the complicated physics involved, aiming at further optimising the technology so that it becomes feasible for scale-up applications and attractive for industrial use. Based on the main USP mechanisms previously studied by in-situ observations coupled with acoustic pressure measurements, i.e. fragmentation, deagglomeration and dispersion of the solid phases and inclusions, technological approaches are suggested and tested for grain refinement upon direct-chill casting of Al alloys. Results showed that USP in the melt flow in the launder significantly improves the as-cast structure of a billet, opening the way for upscaling.